The Evaluation of Injures Caused by Falling According to Forensic Medicine - Tokdemir, Mehmet; Türkoğlu, Abdurrahim; Kafadar, Hüseyin; Deveci, Süleyman Erhan (The Bulletin of Legal Medicine, 2007)
Falls are one of the leading causes of admission to emergency and deaths. There is more than one classification of the falls. In this study we classified falls according to height of the falls: High level (>5 meters) and low level (<5 meters). We didn’t include flat ground falls to our study. In this study, we reviewed 1218 fall cases retrospectively between January 2000 to December 2004 including 779 men and 439 women whose average age is 22.2 + 22.9 (the youngest is 1 age and the oldest is 95 age) years at Firat Medical Center. Nine hundred twenty seven of these cases are low level falls and 213 are high level falls. Of these falls, the level of the fall was not specified in 78 cases. The cases are evaluated according to the sex, age, age groups, the level of fall, simple medical intervention, life threatening, Glasgow Coma Score (GKS), injured body part, mortality and monthly timeframe. Sex and age differences are not significant according to the high and low level fallings (p = 0.1). 37.6% of high level falls are lile threatening compared to 20.4% of low level falls (p=0.0001). Similarly the Glasgow Coma Scores were poorer in high level falls compared to low level falls. The falls are most prevalent among children (59.2%) and lower among adults (32.7%) and elderly (8.1%). We conclude that the falls should be handled with care because of mortality and morbidity risk and burden to health system. It is often seen at childhood therefore the families have to be educated for preventive measures. Also, it is necessary to take some security precautions at the windows and balconies. Keywords: Falling, height, life threatening, glasgow coma score.